Report concerning the All-Ukrainian research/practice conference «Topical Issues of Ophthalmology» (Ukrainian Journal of Ophthalmology, 2025)
The All-Ukrainian research/practice conference "Topical Issues of Ophthalmology" was on September 23-24, 2020. Organizers of this event were SI «The Filatov Institute of Eye Diseases and Tissue Therapy of NAMS of Ukraine», SO «Ukrainian Society of Ophthalmologists», I. Horbachevsky Ternopil National Medical University with the support of the National Academy of Medical Sciences of Ukraine and the Ministry of Health of Ukraine. The event was online on the website region.tou.org.ua.